Resistance of bovine gastrointestinal nematodes to four classes of anthelmintics in the semiarid region of Paraíba state, Brazil - Lídio Ricardo Bezerra de Melo; Luana Carneiro de Sousa; Clarisse Silva de Menezes Oliveira; Felipe Boniedj Ventura Alvares; Larissa Claudino Ferreira; Roberto Alves Bezerra; Ana Célia Rodrigues Athayde; Thais Ferreira Feitosa; Vinícius Longo Ribeiro Vilela (Revista Brasileira de Parasitologia Veterinária, 2021)
Abstract The effectiveness of four anthelmintic classes on cattle gastrointestinal nematodes in the semi-arid region of Paraiba State, Brazil, was evaluated. Twenty farms were used, testing 40 animals in each one, totaling 800 animals. Cattle were divided into four groups composed with ten animals: I, treated with albendazole sulfoxide 15%; II, treated with ivermectin 1%; III, treated with closantel 25%; IV, treated with levamisole hydrochloride 7.5%. All treatments were administered subcutaneously. For the Fecal Egg Count Reduction Test (FECRT), individual fecal samples were collected on days 0 and 14, and sent for analysis of egg count per gram of feces (EPG) and larval cultures. It was observed that multiresistance was present in 95% (19/20) of the farms. Resistance to ivermectin and albendazole was observed in 95% (19/20), to closantel in 75% (15/20) and to levamisole in 20% (4/20). The most used management system was semi-intensive (75%; 15/20) and the ivermectin was the most reported drug for controlling helminths (65%; 13/20). Haemonchus spp. was the most prevalent helminth genus. It was concluded that the anthelmintic resistance of bovine gastrointestinal nematodes is high in the semi-arid of Paraíba State, Brazil, with multiresistance observed mainly to ivermectin, albendazole and closantel.